P260 Autoimmune pancreatitis in patients with Inflammatory Bowel Disease: results from a multicentre ECCO CONFER cases series. (21st January 2022) - Eder, P M; Verstock, B; Culver, E; Dragoni, G; Kredel, L I; de Paredes, A G G; Kaniewska, M; Leibovitzh, H; Oracz, G; Ribaldone, D G; Wypych, J; Badaoui, A; et al.
Abstract: Background: Autoimmune pancreatitis (AIP) is an uncommon inflammatory disorder that may accompany inflammatory bowel disease (IBD). The clinical relevance of AIP-IBD coexistence, therapeutic strategies, and long-term outcomes are scarcely known. Methods: In this ECCO COllaborative Network For Exceptionally Rare case reports project (ECCO-CONFER) we included cases of AIP diagnosed in patients with IBD. Data on the diagnostic criteria, clinical characteristics, and patient outcomes were retrospectively collected and analysed. Results: The cohort included 82 patients [54% males, 77% with ulcerative colitis (UC), age at IBD and AIP diagnosis 32±16 and 35±16 years, respectively]. Of all AIP patients, 71% were classified as type 2, 21% as type 1, and 8% as undefined type. Detailed characteristics of the study group are shown in Table 1. In 57% of the individuals, IBD was diagnosed before AIP. In the remaining cases, IBD was diagnosed simultaneously (20%) or afterwards (23%). Half of the patients required immunomodulators and 43% biological therapy to control their IBD. Twenty-two percent of UC and 6% of Crohn's disease (CD) required surgical intervention during a mean follow-up of 3.6±3.4 years. Histological confirmation was used in 38% of cases, while the remaining were diagnosed as probable AIP based on clinical, biochemical, and radiologic criteria. Magnetic resonance was the most frequently used imaging modality (61%). Eighty percent of patients received steroids for AIP. Thiopurines were used for AIP in 16 (19%) patients, 81% of them responded to treatment. One patient was successfully treated for AIP with infliximab. AIP complications occurred in 27%, including pancreatic exocrine insufficiency (19%) and diabetes (13%). Five patients underwent surgery due to suspected pancreatic cancer. Patients with complicated AIP were significantly older at AIP and IBD diagnosis, were more frequently males and presented with weight loss at AIP diagnosis, and had less frequently a family history of IBD (Table 1). Colonic IBD (i.e. UC, isolated colonic IBD-unclassified or colonic CD) was seen in a higher proportion of individuals with complicated vs benign AIP course (91% vs 33%, p<0.0001). At the end of follow-up, 75 (91%) and 73 (89%) patients were in remission of AIP and IBD, respectively. No IBD or AIP-related deaths were reported. Conclusion: In this large international cohort of patients with concomitant AIP-IBD, most patients have type 2 AIP and colonic IBD. AIP course is relatively benign, and long-term outcomes are favourable. Older age, male gender, isolated colonic IBD location, and weight loss at AIP presentation were seen in higher proportions of patients with a complicated course of AIP.